Kindred Voices - Pifer, Michael. (New Haven ; London)
xii, 302 sayfa
Keywords: “The fascinating story of how premodern Anatolia’s multireligious intersection of cultures shaped its literary languages and poetic masterpieces. By the mid-thirteenth century, Anatolia had become a place of stunning cultural diversity. Kindred Voices explores how the region’s Muslim and Christian poets grappled with the multilingual and multireligious worlds they inhabited, attempting to impart resonant forms of instruction to their intermingled communities. This convergence produced fresh poetic styles and sensibilities, native to no single people or language, that enabled the period’s literature to reach new and wider audiences. This is the first book to study the era’s major Persian, Armenian, and Turkish poets, from roughly 1250 to 1340, against the canvas of this broader literary ecosystem“ --